Ammonia oxidation catalyst as well as preparation method and application thereof

By using a support and supported active components, and using specific preparation methods, the existing catalysts have been solved, and efficient and stable aromatic hydrocarbon ammonia oxidation reaction is achieved, and environmental protection requirements for industrial applications are met.

CN119680595APending Publication Date: 2025-03-25WANHUA CHEM GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411914862.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In actual applications, existing ammonia oxidation catalysts have problems such as low catalyst strength, short life and low reaction activity, which are difficult to meet environmental protection requirements and industrial needs.

Method used

The ammonia oxidation catalyst composed of a carrier and supported active components is composed of a specific preparation method, including vanadium precursor, chromium precursor, element A precursor and water, oxalic acid and support precursor, stirring and mixed with element B precursor and element C precursor, adding polymer and surfactant, aged, spray-dried and high-temperature calcined to produce a high-performance catalyst.

Benefits of technology

It improves the strength and life of the catalyst, enhances its activity, yield and stability in aromatic hydrocarbon ammonia oxidation reaction, and meets the environmental protection requirements in industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005206596500000081
    Figure BDA0005206596500000081
Patent Text Reader

Abstract

The invention provides an ammoxidation catalyst as well as a preparation method and application thereof. The catalyst comprises a carrier and a loaded active component, the active component meets the structural formula V < 1.0 > CraAbBcCdOx by atomic ratio calculation, and the element A is selected from at least one of molybdenum, bismuth, iron, cobalt, nickel and tungsten; the element B is selected from at least one of lithium, sodium, potassium, rubidium and cesium; the C element is selected from at least two of boron, phosphorus, arsenic, tellurium and antimony; a is equal to 0.5-1.8, b is equal to 0.01-2.0, c is equal to 0.001-0.3, d is equal to 0.01-2.0, and x is the sum of the number of oxygen atoms required by valence of other elements in the formula. The catalyst has the problems of low catalyst strength, short service life and low reaction activity when being used for ammoxidation reaction, and can be used for industrial production of m-xylene ammoxidation for preparation of isophthalonitrile catalysts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ammonia oxidation catalysts, and in particular to an aromatic hydrocarbon ammonia oxidation catalyst and a preparation method and application thereof.

[0002] In the field of chemical synthesis, aromatic nitrile compounds have established their position as key intermediates with their unique chemical composition and reaction characteristics. They not only play a fundamental role in the industry of synthetic dyes and fragrances, but also show their versatility and application potential in the fields of organic synthesis, polymer material preparation and medicinal chemistry.

[0003] Take isophthalonitrile as an example. It has excellent chemical structure and reaction performance. Through chlorination reaction, isophthalonitrile can be converted into tetrachloroisophthalonitrile, namely thiophanate-methyl. This compound is widely used in the fields of agriculture and industrial corrosion protection due to its high anti-mold and fungicide performance and low toxicity, providing an effective solution for protecting crops and materials.

[0004] Through further chemical processing, such as hydrogenation, isophthalonitrile can be converted into meta-xylylenediamine, commercially known as MXDA. MXDA is one of the key raw materials for the synthesis of nylon resin. Nylon resin is widely used in industry for its excellent mechanical properties and heat resistance. In the synthesis of nylon resin, MXDA can improve the heat resistance and mechanical strength of the resin, making it suitable for a wider range of application scenarios. At the same time, MXDA is also a key raw material for the synthesis of high-performance polymers such as polyurethane. In the synthesis of polyurethane, MXDA helps to produce polyurethane materials suitable for different applications, such as its application in electronics, automobile manufacturing, and aerospace. In addition, MXDA is also used as a surfactant, paper processing agent, metal chelating agent, rubber crosslinking agent and stabilizer, fiber treatment agent, pesticide, photosensitive resin, lubricant and rust inhibitor, etc.

[0005] In summary, the chemical and industrial value of aromatic nitriles and their derivatives cannot be ignored. With the continuous advancement of chemical synthesis technology, it can be expected that aromatic nitrile compounds will play a more critical role in future chemical research and industrial applications, contributing more innovation and value to the development of human society.

[0006] The simplest and most economical method for producing aromatic nitrile is to obtain it by gas phase ammoxidation of aromatic hydrocarbons in the presence of a catalyst, the core of which is the use of ammoxidation catalysts. Among them, the most widely used catalyst in industrial applications is the V-Cr fluidized bed catalyst. In recent years, with the expansion of the market for chlorothalonil and MXDA, the production scale of isophthalonitrile in my country has also shown a rapid growth trend, and the research on the corresponding catalysts and their production technologies has also received more attention.

[0007] In the preparation of catalysts, the wear resistance of the catalyst and the cost of raw materials are two important considerations. Therefore, previous patented technologies mainly optimize these two aspects. However, with the improvement of environmental protection requirements, it is becoming more and more important to reduce the degree of deep oxidation of the reaction raw materials, reduce the selectivity of small molecule products such as carbon dioxide and carbon monoxide, and increase the wear resistance of the catalyst and extend the life of the catalyst. Some existing technologies improve the activity and stability of the catalyst by changing the active components of the catalyst or adding different additives. In addition, there are some technologies that improve the wear resistance and mechanical strength of the catalyst by improving the molding and preparation process of the catalyst.

[0008] Although the existing technology has optimized the wear resistance and raw material cost of ammonia oxidation catalysts to a certain extent, in practical applications, there are still problems such as low catalyst strength, short life and low reaction activity. Summary of the invention

[0009] In view of the problems existing in the above-mentioned prior art, one of the objects of the present invention is to provide an ammonia oxidation catalyst and a preparation method thereof, wherein the catalyst has good strength, long life and a simple preparation method.

[0010] A second object of the present invention is to provide an application of the above-mentioned ammoxidation catalyst in the preparation of aromatic nitriles by ammoxidation of aromatic hydrocarbons, which has the advantages of high activity, good yield and stability when used in the ammoxidation reaction.

[0011] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:

[0012] In a first aspect, the present invention provides an ammonia oxidation catalyst, the catalyst comprising a carrier and a supported active component;

[0013] The active component, calculated by atomic ratio, satisfies the following structural formula

[0014] V 1.0 Cr a A b B c C d O x ,in:

[0015] Element A is selected from at least one of molybdenum, bismuth, iron, cobalt, nickel and tungsten;

[0016] The B element is at least one selected from lithium, sodium, potassium, rubidium and cesium;

[0017] The C element is selected from at least two of boron, phosphorus, arsenic, tellurium and antimony;

[0018] a=0.5~1.8, preferably 0.8~1.5;

[0019] b = 0.01 to 2.0, preferably 0.01 to 1.0;

[0020] c = 0.001 to 0.3, preferably 0.001 to 0.15;

[0021] d = 0.01 to 2.0, preferably 0.01 to 1.5;

[0022] The value of x is the sum of the number of oxygen atoms required to satisfy the valence of other elements in the formula. In practical applications, the value of x is about 3 to 20;

[0023] Specifically, the value of a can be 0.5, 0.7, 0.9, 1.0, 1.2, 1.4, 1.6, 1.8 or a range between any two of them;

[0024] The value of b may be 0.01, 0.05, 0.1, 0.3, 0.5, 0.7, 1.0, 1.2, 1.5, 1.7, 2.0 or a range between any two thereof;

[0025] The value of c can be 0.001, 0.005, 0.01, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3 or a range between any two thereof;

[0026] The value of d can be 0.01, 0.05, 0.1, 0.3, 0.5, 0.7, 1.0, 1.2, 1.5, 1.7, 2.0 or a range between any two of them.

[0027] In one embodiment of the present invention, the carrier is an inorganic carrier, preferably any one of silicon dioxide, hydroxyapatite, sodium silicate, titanium dioxide, zirconium dioxide, or a combination of at least two thereof.

[0028] In one embodiment of the present invention, the content of the carrier is 25 to 70 wt % based on the total weight of the ammoxidation catalyst.

[0029] In one embodiment of the present invention, the wear index of the ammonia oxidation catalyst is ≤1.5%, such as 1.5%, 1.3%, 1.1%, 1.0%, 0.8%, 0.6%, 0.4%, 0.2%, 0.1%, etc., preferably ≤1.1%.

[0030] In one embodiment of the present invention, the specific surface area of ​​the ammonia oxidation catalyst is 15 to 110 m 2 / g, including but not limited to 15m 2 / g, 30m 2 / g, 45m 2 / g, 60m 2 / g, 75m2 / g, 90m 2 / g、100m 2 / g, 110m 2 / g or a range consisting of any two of them, preferably 25 to 65 m 2 / g.

[0031] In one embodiment of the present invention, the mesopore volume of the ammonia oxidation catalyst is 0.1 to 0.55 cm 3 / g, including but not limited to 0.1cm 3 / g, 0.15cm 3 / g, 0.2cm 3 / g, 0.25cm 3 / g, 0.3cm 3 / g, 0.35cm 3 / g or, 0.4cm 3 / g, 0.45cm 3 / g, 0.5cm 3 / g, 0.55cm 3 / g or a range consisting of any two of them, preferably 0.15 to 0.35 cm 3 / g.

[0032] In a second aspect, the present invention provides a method for preparing the above-mentioned ammonia oxidation catalyst, the method comprising the following steps:

[0033] S1: Mix a vanadium precursor, a chromium precursor, an element A precursor and water, then add oxalic acid, stir to obtain a solution, then add a carrier precursor, stir to obtain slurry 1;

[0034] S2: dissolving the B element precursor and the C element precursor in water, then adding the carrier precursor, stirring to obtain a slurry, then adding a polymer and a surfactant, aging for a period of time, and obtaining slurry 2;

[0035] S3: mixing slurry 1 and slurry 2, heating to evaporate water, and obtaining concentrated slurry;

[0036] S4: spray drying the concentrated slurry and calcining at high temperature to obtain the ammonia oxidation catalyst.

[0037] In one embodiment of the present invention, the vanadium precursor in step S1 is selected from any one of vanadium pentoxide, vanadium tetroxide, vanadium trioxide, ammonium metavanadate, sodium metavanadate, or a combination of at least two thereof.

[0038] In one embodiment of the present invention, the chromium precursor in step S1 is selected from any one of sodium dichromate, chromic anhydride, potassium dichromate, chromium trioxide, and chromous oxide, or a combination of at least two thereof.

[0039] In one embodiment of the present invention, the element A precursor in step S1, wherein the element A is at least one of molybdenum, bismuth, iron, cobalt, nickel, and tungsten;

[0040] Preferably, the element A precursor is selected from a soluble compound containing element A, preferably any one of element A oxide, element A nitrate, element A acetate, and element A soluble inorganic salt, or a combination of at least two thereof.

[0041] In one embodiment of the present invention, the oxalic acid in step S1 can be added directly as a pure product, or can be dissolved in water to prepare a solution with a concentration of 20-70 wt% and then added. The specific form of addition can be determined according to actual needs and is not limited by the present invention.

[0042] In one embodiment of the present invention, in step S1, the carrier precursor is added and stirred to obtain slurry 1, wherein the stirring time is 1 to 5 hours and the temperature is 75 to 95°C. Specifically, the time can be 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h or a range consisting of any two thereof, and the temperature can be 75°C, 78°C, 80°C, 82°C, 85°C, 88°C, 90°C, 92°C, 95°C or a range consisting of any two thereof.

[0043] In one embodiment of the present invention, the carrier precursor in steps S1 and S2 is a compound that can form the carrier described above after high-temperature calcination in step S4, wherein the carrier is preferably any one of silicon dioxide, hydroxyapatite, sodium silicate, titanium dioxide, and zirconium dioxide, or a combination of at least two thereof. Correspondingly, its precursor is selected from any one of silica sol, hydroxyapatite, water glass, titanium dioxide, and zirconium dioxide, or a combination of at least two thereof.

[0044] In one embodiment of the present invention, the B element precursor in step S2, wherein the B element is at least one of lithium, sodium, potassium, rubidium, and cesium;

[0045] Preferably, the B element precursor is selected from a soluble compound containing the B element, preferably any one of a soluble oxide of the B element, a nitrate of the B element, an acetate of the B element, and a sulfate of the B element, or a combination of at least two thereof.

[0046] In one embodiment of the present invention, the C element precursor in step S2, wherein the C element is at least two of boron, phosphorus, arsenic, tellurium, and antimony;

[0047] Preferably, the C element precursor is selected from soluble compounds containing C element, preferably a combination of at least two C elements among soluble oxides of C element, nitrates of C element, and inorganic acids containing C element.

[0048] In one embodiment of the present invention, the polymer in step S2 is selected from any one of polylactic acid, polyvinyl alcohol, polytetramethylene ether glycol, polybutylene succinate, or a combination of at least two thereof.

[0049] In one embodiment of the present invention, the surfactant in step S2 is selected from any one of polyethylene glycol, benzalkonium chloride, lauric acid, and sodium secondary alkyl sulfonate, or a combination of at least two thereof.

[0050] In one embodiment of the present invention, the vanadium precursor, chromium precursor, element A precursor in step S1, and the element B precursor and element C precursor in step S2 are used in amounts that meet the active component structural formula V 1.0 Cr a A b B c C d O x ; Specifically, the amounts of the vanadium precursor, chromium precursor, element A precursor, element B precursor, and element C precursor are calculated based on the vanadium, chromium, element A, element B, and element C therein, respectively, in a molar ratio of 1.0: (0.5-1.8): (0.01-2.0): (0.001-0.3): (0.01-2.0), preferably 1.0: (0.8-1.5): (0.01-1.0): (0.001-0.15): (0.01-1.5).

[0051] In one embodiment of the present invention, in step S1, the mass ratio of the vanadium precursor to oxalic acid is 1:0.1-15, including but not limited to 1:0.1, 1:0.5, 1:1, 1:3, 1:5, 1:7, 1:10, 1:12, 1:15 or a range consisting of any two thereof; the mass ratio of the vanadium precursor to the carrier precursor is 1:0.5-50, including but not limited to 1:0.5, 1:10, 1:20, 1:30, 1:40, 1:50 or a range consisting of any two thereof;

[0052] The mass ratio of the carrier precursor added in step S1 and step S2 is 1:0.5-2, including but not limited to 1:0.5, 1:0.6, 1:0.7, 1:1.1, 1:1.3, 1:1.5, 1:2.0 or a range consisting of any two thereof;

[0053] In step S2, the mass ratio of the polymer to the vanadium precursor in step S1 is 0.001 to 0.1:1, including but not limited to 0.001:1, 0.005:1, 0.01:1, 0.03:1, 0.05:1, 0.08:1, 0.1:1 or a range consisting of any two thereof; the mass ratio of the polymer to the surfactant is 0.01 to 20:1, including but not limited to 0.01:1, 0.1:1, 1:1, 3:1, 5:1, 8:1, 10:1, 12:1, 15:1, 18:1, 20:1 or a range consisting of any two thereof, preferably 0.01 to 10:1;

[0054] The water described in steps S1 and S2 is used to dissolve the soluble precursor raw materials to form a solution, which is evaporated and removed after the catalyst is formed. The amount used is not limited. Technicians in the field can operate according to experience to achieve the purpose of dissolution. The present invention does not make specific limitations here.

[0055] In one embodiment of the present invention, the aging in step S2 is performed at a temperature of 75 to 95°C, preferably 80-95°C; and for a time of 0.5 to 96h, preferably 0.5 to 72h. Specifically, the temperature may be 75°C, 78°C, 80°C, 82°C, 85°C, 88°C, 90°C, 92°C, 95°C or a range consisting of any two thereof, and the time may be 0.5h, 1h, 10h, 20h, 30h, 40h, 50h, 60h, 70h, 80h, 90h or a range consisting of any two thereof.

[0056] In one embodiment of the present invention, the evaporation in step S3 is carried out at a temperature of 60 to 120°C, including but not limited to 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C or a range between any two thereof, preferably 70 to 110°C;

[0057] Preferably, the evaporation end point is to form a concentrated slurry with a solid content of 25 to 60 wt%.

[0058] In one embodiment of the present invention, the viscosity of the concentrated slurry in step S3 is 150 to 1000 mPa·s, preferably 150 to 850 mPa·s.

[0059] In one embodiment of the present invention, the spray drying in step S3, the temperature of the slurry during the spraying process (i.e., the concentrated slurry in step S3) is 30-100°C, including but not limited to 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C or a range between any two thereof, preferably 35-95°C;

[0060] Preferably, the inlet temperature of the spray process is 150-250°C, and the outlet temperature is 90-130°C.

[0061] In one embodiment of the present invention, the high temperature calcination in step S4, the calcination temperature is 450-750°C, and the calcination time is 1-15h. Specifically, the temperature can be 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or a range consisting of any two thereof, and the time can be 1h, 3h, 5h, 8h, 10h, 12h, 15h or a range consisting of any two thereof;

[0062] Preferably, the calcination heating rate is 1 to 5°C / min, including but not limited to 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min or a range consisting of any two thereof.

[0063] In a third aspect, the present invention also provides the use of the ammonia oxidation catalyst prepared by the method described above.

[0064] A use of an ammoxidation catalyst, wherein the catalyst is obtained by the above-mentioned preparation method, or is the above-mentioned catalyst, and the catalyst is used for preparing aromatic nitriles by ammoxidation of aromatic hydrocarbons, for example, aromatic hydrocarbon raw materials such as m-xylene, p-xylene, o-xylene, toluene, etc., and the corresponding nitrile products are prepared by ammoxidation reaction, and is preferably used for preparing isophthalonitrile from m-xylene.

[0065] In one embodiment, the method for preparing aromatic nitriles by ammoxidation of aromatic hydrocarbons as described above can refer to existing processes and carry out ammoxidation reaction by a conventional reactor in the art. For example, the reactor used can be a fluidized bed reactor or a fixed bed tank reactor.

[0066] Specifically, a method for preparing aromatic nitrile by ammoxidation of aromatic hydrocarbons comprises the following steps:

[0067] The ammonia oxidation catalyst is loaded into a fluidized bed reactor for reaction, the reaction raw material feed ratio is aromatic hydrocarbon: ammonia: air molar ratio of 1:4.5-6.5:25-40, the reaction temperature is 300-450°C, the reaction pressure is 10-100 kPaG; the weight load of the ammonia oxidation catalyst in the reactor is 0.04-0.08 h -1 .

[0068] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in:

[0069] (1) The present invention can effectively improve the pore structure of the catalyst, stabilize the active components, and increase the life of the catalyst by pre-treating a portion of the carrier with a surfactant, and then subjecting the carrier to aging and appropriate calcination processes.

[0070] (2) The present invention can stably produce high-performance industrial catalysts and ensure their excellent mechanical strength, catalytic activity and stability by mixing a portion of the carrier slurry pretreated with a surfactant with the remaining carrier slurry that has not been pretreated, and controlling the spray drying slurry viscosity and roasting process during the catalyst preparation process.

[0071] (3) The catalyst of the present invention has the advantages of high activity, good yield and stability when used in ammoxidation reaction. DETAILED DESCRIPTION

[0072] The following examples will further illustrate the method provided by the present invention, but the present invention is not limited to the listed examples, and should also include any other known changes within the scope of the rights claimed by the present invention.

[0073] Unless otherwise specified, the reagents, materials and instruments used in the following examples are conventional reagents, conventional materials and conventional instruments in the art and can be obtained commercially. The reagents involved can also be synthesized by conventional methods in the art.

[0074] The metal salt raw materials used in the embodiments or comparative examples of the present invention are all purchased from Beijing Inokai Technology Co., Ltd., and other raw materials are also commercially available raw materials unless otherwise specified.

[0075] Testing and characterization of various parameters of the catalyst in the embodiments or comparative examples of the present invention:

[0076] 1. Determination method of catalyst wear index (straight tube method):

[0077] The wear index was determined according to the method in the standard “Straight tube method for determination of wear index of catalytic cracking catalyst” Q / TSH3490909 2006.

[0078] 2. Determination of catalyst specific surface area and pore structure information

[0079] The BET specific surface area, BJH desorption pore volume and pore size of the catalyst were measured by N2 physical adsorption method using Micrometics ASAP 2460 as the testing instrument.

[0080] 3. Method for determining catalyst slurry viscosity

[0081] The Shanghai Changji NDJ-1B rotational viscometer was used for the measurement. No. 3 rotor was selected and the rotation speed was 60 rpm.

[0082] 4. The calculation formulas for the conversion rate of meta-xylene and the selectivity of the target product isophthalonitrile are as follows:

[0083]

[0084] The following is a detailed description of the present invention through specific embodiments.

[0085] Example 1

[0086] 1) Preparation of ammonia oxidation catalyst

[0087] S1: 298 g (3.28 mol vanadium) of vanadium pentoxide, 312 g (3.12 mol chromium) of chromium trioxide, and 124 g (0.7 mol molybdenum) of ammonium molybdate tetrahydrate were placed in 320 g of water, heated to 80°C, and a solution obtained by dissolving 1800 g of oxalic acid in 1900 g of water was slowly added under stirring, and 1500 g of 30 wt% silica sol was added, and the mixture was stirred for 1 h to obtain slurry 1.

[0088] S2: 16.2 g (0.19 mol sodium) sodium nitrate, 41 g (0.66 mol boron) boric acid, and 15.1 g (0.13 mol phosphorus) 85 wt% phosphoric acid were dispersed in 200 g water, heated to 90°C, 1000 g 40 wt% silica sol was added with stirring to obtain a slurry, 5.5 g polylactic acid and 4 g PEG-200 were added thereto, and aged for 30 min to obtain slurry 2.

[0089] S3: Slurry 1 and slurry 2 were mixed, and the water was removed by evaporation and concentration at 100°C. When the solid content reached 35wt%, the concentration was stopped to obtain a concentrated slurry. The concentrated slurry was cooled to 85°C, and the viscosity was tested to be 310mPa·s.

[0090] S4: The concentrated slurry was spray dried at an inlet temperature of 190°C and an outlet temperature of 105°C to obtain a catalyst precursor; the obtained catalyst precursor was placed in a muffle furnace, heated to 590°C at a heating rate of 2°C / min, kept warm for 10 hours, and finally cooled to room temperature to obtain an ammonia oxidation catalyst. The specific surface area of ​​the catalyst was 69m 2 / g, and the mesopore volume is 0.29cm 3 / g.

[0091] The active component in the above catalyst has a structural formula of V in terms of atomic ratio. 1.0 Cr 0.95 Mo 0.2 Na 0.06 B 0.2 P 0.04 O x , x is taken as 4.955 (the sum of the number of oxygen atoms required to satisfy the valence of other elements), the carrier is SiO2, the content of the carrier is 51wt% based on the total weight of the ammonia oxidation catalyst, and the catalyst wear index is measured to be 0.73%.

[0092] 2) Ammoxidation of m-xylene

[0093] 300 g of the ammonia oxidation catalyst obtained above was loaded into a fluidized bed reactor for reaction performance evaluation. The molar ratio of the reaction raw materials was m-xylene: ammonia: air was 1:5.5:37, the reaction temperature was 390 ° C, the reaction pressure was 40 kPaG, and the catalyst weight load in the reactor was 0.06 h -1 .

[0094] After 12 hours of reaction, sampling was conducted, and the conversion rate of meta-xylene was 99.2%, and the selectivity of meta-dibenzonitrile was 92.3%. After 500 hours of continuous reaction, sampling was conducted, and the conversion rate of meta-xylene was 99.0%, and the selectivity of meta-dibenzonitrile was 89.1%.

[0095] Example 2

[0096] 1) Preparation of catalyst

[0097] S1: 1210 g (10.3 mol vanadium) ammonium metavanadate, 400 g (5.26 mol chromium) chromium trioxide, 17.2 g (0.103 mol molybdenum) ammonium heptamolybdate, and 25.8 g (0.1 mol nickel) nickel acetate tetrahydrate were placed in 320 g water, heated to 80°C, and a solution obtained by dissolving 1955 g oxalic acid in 2000 g water was slowly added under stirring, and 600 g zirconium dioxide was added, and the mixture was stirred for 1 h to obtain slurry 1.

[0098] S2: Disperse 1.1 g (0.011 mol potassium) potassium acetate, 4.6 g (0.1 mol boron) metaboric acid, and 31 g (0.1 mol antimony) antimony acetate in 10 g water, heat to 90°C, add 400 g zirconium dioxide with stirring to obtain a slurry, then add 10 g polyvinyl alcohol and 20 g lauric acid thereto, and age for 6 hours to obtain slurry 2.

[0099] S3: Slurry 1 and slurry 2 were mixed, and the water was removed by evaporation and concentration at 100°C. When the solid content reached 28wt%, the concentration was stopped to obtain a concentrated slurry. The concentrated slurry was cooled to 40°C, and the viscosity was tested to be 212mPa·s.

[0100] S4: The concentrated slurry was spray dried at an inlet temperature of 250°C and an outlet temperature of 120°C to obtain a catalyst precursor; the obtained catalyst precursor was placed in a muffle furnace, heated to 470°C at a heating rate of 1°C / min, kept warm for 2 hours, and finally cooled to room temperature to obtain an ammonia oxidation catalyst. The specific surface area of ​​the catalyst was 58m by BET test. 2 / g, and the mesopore volume is 0.27cm 3 / g.

[0101] The active component in the above catalyst has a structural formula of V in terms of atomic ratio. 1.0 Cr 0.5 Mo 0.01 Ni 0.01 K 0.001 B 0.01 Sb 0.01 O x , x is 3.32 (the sum of the number of oxygen atoms required to satisfy the valence of other elements), the carrier is ZrO2, the content of the carrier is 40wt% based on the total weight of the ammonia oxidation catalyst, and the catalyst wear index is measured to be 0.71%.

[0102] 2) Ammoxidation of m-xylene

[0103] 300 g of the ammonia oxidation catalyst obtained above was loaded into a fluidized bed reactor for reaction performance evaluation. The reaction raw material feed ratio was m-xylene: ammonia: air at a molar ratio of 1:5:25, the reaction temperature was 390 ° C, the reaction pressure was 30 kPaG, and the catalyst weight load in the reactor was 0.04 h -1 .

[0104] After 12 hours of reaction, sampling was conducted, and the conversion rate of meta-xylene was 98.1%, and the selectivity of meta-dibenzonitrile was 87.1%. After 500 hours of continuous reaction, sampling was conducted, and the conversion rate of meta-xylene was 98.0%, and the selectivity of meta-dibenzonitrile was 86.3%.

[0105] Example 3

[0106] 1) Preparation of ammonia oxidation catalyst

[0107] S1: 182 g (2 mol vanadium) vanadium pentoxide, 361 g (3.61 mol chromium) chromium trioxide, 445 g (1.81 mol iron) ferric acetate tetrahydrate, and 553 g (1.9 mol nickel) nickel nitrate hexahydrate are placed in 2000 g water, heated to 80°C, and a solution obtained by dissolving 1750 g oxalic acid in 2000 g water is slowly added under stirring, and 2000 g titanium dioxide is added, and the mixture is stirred for 1 hour to obtain slurry 1.

[0108] S2: Disperse 50 g (0.6 mol sodium) of sodium nitrate, 210 g (1.82 mol phosphorus) of 85% phosphoric acid, and 261 g (1.79 mol antimony) of antimony trioxide in 500 g of water, heat to 85°C, add 2000 g of titanium dioxide with stirring to obtain a slurry, then add 6.6 g of polybutylene succinate and 0.33 g of sodium secondary alkyl sulfonate, and age for 3 hours to obtain slurry 2.

[0109] S3: Slurry 1 and slurry 2 were mixed, and the water was removed by evaporation and concentration at 95°C. When the solid content reached 60wt%, the concentration was stopped to obtain a concentrated slurry. The concentrated slurry was cooled to 85°C, and the viscosity was tested to be 812mPa·s.

[0110] S4: The concentrated slurry was spray dried at an inlet temperature of 245°C and an outlet temperature of 120°C to obtain a catalyst precursor; the obtained catalyst precursor was placed in a muffle furnace, heated to 700°C at a heating rate of 5°C / min, kept warm for 14 hours, and finally cooled to room temperature to obtain an ammonia oxidation catalyst. The specific surface area of ​​the catalyst was 48m 2 / g, and the mesopore volume is 0.44cm 3 / g.

[0111] The active component in the above catalyst has a structural formula of V in terms of atomic ratio. 1.0 Cr 1.8 Ni 0.9 Fe 0.9 Na 0.3 P 0.9 Sb 0.9 O x , x is 11.2 (the sum of the number of oxygen atoms required to satisfy the valence of other elements), the carrier is TiO2, the content of the carrier is 66wt% based on the total weight of the ammonia oxidation catalyst, and the catalyst wear index is measured to be 0.88%.

[0112] 2) Ammoxidation of m-xylene

[0113] 300 g of the ammonia oxidation catalyst obtained above was loaded into a fluidized bed reactor for reaction performance evaluation. The molar ratio of the reaction raw materials was m-xylene: ammonia: air was 1:6.5:39, the reaction temperature was 430 ° C, the reaction pressure was 90 kPaG, and the catalyst weight load in the reactor was 0.08 h -1 .

[0114] After 12 hours of reaction, sampling was conducted, and the conversion rate of meta-xylene was 99.4%, and the selectivity of meta-dibenzonitrile was 86.9%. After 500 hours of continuous reaction, sampling was conducted, and the conversion rate of meta-xylene was 98.9%, and the selectivity of meta-dibenzonitrile was 85.2%.

[0115] Comparative Example 1

[0116] The method of Example 1 is followed, except that polylactic acid is not added in step S2 during the preparation of the catalyst, and other operations remain unchanged.

[0117] 1) The active component in the prepared catalyst has a structural formula of V in terms of atomic ratio 1.0 Cr 0.95 Mo 0.7Na 0.06 B 0.2 P 0.04 O x The carrier is SiO2, and the content of the carrier is 51wt% based on the total weight of the ammonia oxidation catalyst. The catalyst attrition index is measured to be 0.98%.

[0118] 2) Ammoxidation reaction of m-xylene, the conversion rate of m-xylene was 99.0%, and the selectivity of m-dibenzonitrile was 91.1%; sampling was taken after 500 hours of continuous reaction, the conversion rate of m-xylene was 97.1%, and the selectivity of m-dibenzonitrile was 77.3%.

[0119] Comparative Example 2

[0120] The method of Example 1 is followed, except that PEG-200 is not added in step S2 during the preparation of the catalyst, and other operations remain unchanged.

[0121] 1) The active component in the prepared catalyst has a structural formula of V in terms of atomic ratio 1.0 Cr 0.95 Mo 0.7 Na 0.06 B 0.2 P 0.04 O x The carrier is SiO2, and the content of the carrier is 51wt% based on the total weight of the ammonia oxidation catalyst. The catalyst attrition index is measured to be 1.66%.

[0122] 2) In the ammoxidation reaction of m-xylene, the conversion rate of m-xylene was 98.2%, and the selectivity of m-dibenzonitrile was 90.1%. After 500 hours of continuous reaction, the sampling was conducted, and the conversion rate of m-xylene was 97.6%, and the selectivity of m-dibenzonitrile was 74.7%.

[0123] Comparative Example 3

[0124] The method of Example 1 is followed, except that in the process of preparing the catalyst, sodium nitrate is not added in step S2, and other operations remain unchanged.

[0125] 1) The active component in the prepared catalyst has a structural formula of V in terms of atomic ratio 1.0 Cr 0.95 Mo 0.7 B 0.2 P 0.04 O x The carrier is SiO2, and the content of the carrier is 51wt% based on the total weight of the ammonia oxidation catalyst. The catalyst attrition index is measured to be 2.55%.

[0126] 2) In the ammoxidation reaction of m-xylene, the conversion rate of m-xylene was 95.2%, and the selectivity of m-dibenzonitrile was 77.1%. After 500 hours of continuous reaction, the sampling was conducted, and the conversion rate of m-xylene was 93.6%, and the selectivity of m-dibenzonitrile was 56.1%.

[0127] Although the present invention has been described in detail for the purpose of illustration in the foregoing text, it should be understood that these detailed descriptions are only for illustration and can be modified by those skilled in the art without departing from the spirit and scope of the present invention. The present invention is limited only by the claims.

Claims

1. An ammonia oxidation catalyst, characterized in that The catalyst comprises a carrier and a supported active component; The active component, calculated by atomic ratio, satisfies the following structural formula V 1.0 Cr a A b B c C d O x ,in: Element A is selected from at least one of molybdenum, bismuth, iron, cobalt, nickel and tungsten; The B element is at least one selected from lithium, sodium, potassium, rubidium and cesium; The C element is selected from at least two of boron, phosphorus, arsenic, tellurium and antimony; a=0.5~1.8, preferably 0.8~1.5; b = 0.01 to 2.0, preferably 0.01 to 1.0; c = 0.001 to 0.3, preferably 0.001 to 0.15; d = 0.01 to 2.0, preferably 0.01 to 1.5; The value of x is the sum of the number of oxygen atoms required to satisfy the valence of other elements in the formula.

2. The ammonia oxidation catalyst according to claim 1, characterized in that The carrier is an inorganic carrier, preferably any one of silicon dioxide, hydroxyapatite, sodium silicate, titanium dioxide, zirconium dioxide or a combination of at least two thereof; and / or The content of the carrier is 25 to 70 wt % based on the total weight of the ammoxidation catalyst.

3. The ammonia oxidation catalyst according to claim 1, characterized in that The wear index of the ammonia oxidation catalyst is ≤1.5%, preferably ≤1.1%; and / or The specific surface area of ​​the ammonia oxidation catalyst is 15 to 110 m 2 / g, preferably 25 to 65 m 2 / g; and / or The mesopore volume of the ammonia oxidation catalyst is 0.1 to 0.55 cm 3 / g, preferably 0.15 to 0.35 cm 3 / g.

4. A method for preparing the ammonia oxidation catalyst according to any one of claims 1 to 3, characterized in that: The following steps are included: S1: Mix a vanadium precursor, a chromium precursor, an element A precursor and water, then add oxalic acid, stir to obtain a solution, then add a carrier precursor, stir to obtain slurry 1; S2: dissolving the B element precursor and the C element precursor in water, then adding the carrier precursor, stirring to obtain a slurry, then adding a polymer and a surfactant, aging for a period of time, and obtaining slurry 2; S3: mixing slurry 1 and slurry 2, heating to evaporate water, and obtaining concentrated slurry; S4: spray drying the concentrated slurry and calcining at high temperature to obtain the ammonia oxidation catalyst.

5. The preparation method according to claim 4, characterized in that: The vanadium precursor in step S1 is selected from any one of vanadium pentoxide, vanadium tetroxide, vanadium trioxide, ammonium metavanadate, sodium metavanadate, or a combination of at least two thereof; and / or The chromium precursor in step S1 is selected from any one of sodium dichromate, chromic anhydride, potassium dichromate, chromium trioxide, and chromous oxide, or a combination of at least two thereof; and / or The element A precursor in step S1, wherein the element A is at least one of molybdenum, bismuth, iron, cobalt, nickel, and tungsten; Preferably, the element A precursor is selected from a soluble compound containing element A, preferably any one of element A oxide, element A nitrate, element A acetate, and element A soluble inorganic salt, or a combination of at least two thereof.

6. The preparation method according to claim 4, characterized in that: In step S1, the stirring time is 1 to 5 hours at a temperature of 75 to 95° C.; and / or The carrier precursor in steps S1 and S2 is selected from any one of silica sol, hydroxyapatite, water glass, titanium dioxide, and zirconium dioxide, or a combination of at least two thereof.

7. The preparation method according to claim 4, characterized in that: The B element precursor in step S2, wherein the B element is at least one of lithium, sodium, potassium, rubidium, and cesium; Preferably, the B element precursor is selected from a soluble compound containing the B element, preferably any one of a soluble oxide of the B element, a nitrate of the B element, an acetate of the B element, a sulfate of the B element, or a combination of at least two thereof; and / or The C element precursor in step S2, wherein the C element is at least two of boron, phosphorus, arsenic, tellurium, and antimony; Preferably, the C element precursor is selected from a soluble compound containing the C element, preferably a soluble oxide of the C element, a nitrate of the C element, and a combination of at least two C elements in an inorganic acid containing the C element; and / or The polymer in step S2 is selected from any one of polylactic acid, polyvinyl alcohol, polytetramethylene glycol, polybutylene succinate or a combination of at least two thereof; and / or The surfactant in step S2 is selected from any one of polyethylene glycol, benzalkonium chloride, lauric acid, and sodium secondary alkyl sulfonate, or a combination of at least two thereof.

8. The preparation method according to claim 4, characterized in that: The amounts of the vanadium precursor, chromium precursor, element A precursor, element B precursor, and element C precursor in step S1 and step S2 are calculated based on the vanadium, chromium, element A, element B, and element C, respectively, in a molar ratio of 1.0: (0.5-1.8): (0.01-2.0): (0.001-0.3): (0.01-2.0), preferably 1.0: (0.8-1.5): (0.01-1.0): (0.001-0.15): (0.01-1.5); and / or In step S1, the mass ratio of the vanadium precursor to oxalic acid is 1:0.5-15; the mass ratio of the vanadium precursor to the carrier precursor is 1:0.1-50; and / or The mass ratio of the carrier precursor added in step S1 to step S2 is 1:0.5-2; and / or In step S2, the mass ratio of the polymer to the vanadium precursor in step S1 is 0.001-0.1:1; the mass ratio of the polymer to the surfactant is 0.01-20:1, preferably 0.01-10:

1.

9. The preparation method according to claim 4, characterized in that: The aging in step S2 is performed at a temperature of 75 to 95° C., preferably 80 to 95° C., for a time of 0.5 to 96 hours, preferably 0.5 to 72 hours; and / or The evaporation in step S3 is performed at a temperature of 60 to 120° C., preferably 70 to 110° C.; Preferably, the evaporation end point is to form a concentrated slurry with a solid content of 25 to 60 wt%; and / or In the spray drying in step S4, the slurry temperature during the spraying process is 30 to 100° C., preferably 35 to 95° C.; Preferably, the spray process inlet temperature is 150-250°C, and the outlet temperature is 90-130°C; and / or The high temperature calcination in step S4 has a calcination temperature of 450 to 750° C. and a calcination time of 1 to 15 hours; Preferably, the calcination heating rate is 1-5°C / min.

10. Use of an ammonia oxidation catalyst, the catalyst being the ammonia oxidation catalyst according to any one of claims 1 to 3, or being prepared by the method according to any one of claims 4 to 9, the catalyst being used for the ammonia oxidation of aromatic hydrocarbons to prepare aromatic nitriles; the aromatic hydrocarbons are preferably m-xylene, p-xylene, o-xylene, and toluene; Preferably, meta-xylene is used to prepare isophthalonitrile.